Constipation as a possible predictor of poor treatment response in chronic migraine: A retrospective study of anti-calcitonin gene-related peptide (anti-CGRP) monoclonal antibodies and the impact of switching - Sena Uzun; Ulf Frejvall; Per Petersson; Gürdal Sahin (SAGE Publishing, 2024)
Background There is a growing awareness of constipation being a side effect of anti-calcitonin gene-related peptide (anti-CGRP) monoclonal antibodies (mAbs). This study aims to assess constipation as a side effect and explore its potential role as a predictor of treatment response in chronic migraine (CM) patients treated with anti-CGRP mAbs. Methods We conducted a retrospective analysis of patients with CM treated with anti-CGRP mAbs between January 2019 and December 2022 at a single center. Data on patient demographics, migraine characteristics, and constipation were reviewed. Results Among 317 patients, 192 received erenumab, 94 received fremanezumab, and 31 received galcanezumab. Constipation was significantly more common with erenumab (51.5%) compared to fremanezumab (4.2%) and galcanezumab (12.9%). Among erenumab patients, 24.4% switched due to constipation, while 19.2% switched due to lack/loss of effectiveness. Patients who switched treatment experienced milder symptoms ( p  < 0.0001) without compromising effectiveness, even when switching due to lack/loss of effectiveness ( p  = 0.0068). Importantly, severe constipation rates were higher in non-responders ( p  = 0.036). Conclusion Constipation is a notable side effect of anti-CGRP mAbs, particularly with erenumab in CM. Side effect monitoring is consequently crucial. Our findings suggest a potential link between poor treatment response and constipation, warranting further research into the underlying mechanisms.